Weather, Disease, and Wheat Breeding Effects on Kansas Wheat Varietal Yields, 1985 to 2011. (1st January 2014) - Barkley, Andrew; Tack, Jesse; Nalley, Lawton Lanier; Bergtold, Jason; Bowden, Robert; Fritz, Allan
Abstract : Wheat ( Triticum aestivum L.) yields in Kansas have increased due to wheat breeding and improved agronomic practices, but are subject to climate and disease challenges. The objective of this research is to quantify the impact of weather, disease, and genetic improvement on wheat yields of varieties grown in 11 locations in Kansas from 1985 to 2011. Wheat variety yield data from Kansas performance tests were matched with comprehensive location‐specific disease and weather data, including seasonal precipitation, monthly air temperature, air temperature and solar radiation around anthesis, and vapor pressure deficit (VPD). The results show that wheat breeding programs increased yield by 34 kg ha –1 yr –1 . From 1985 through 2011, wheat breeding increased average wheat yields by 917 kg ha –1, or 27% of total yield. Weather was found to have a large impact on wheat yields. Simulations demonstrated that a 1°C increase in projected mean temperature was associated with a decrease in wheat yields of 715 kg ha –1, or 21%. Weather, diseases, and genetics all had significant impacts on wheat yields in 11 locations in Kansas during 1985 to 2011.